Description of the pupa and observations on the distribution, ecology, and life history of Quedius spelaeus spelaeus Horn (Coleoptera: Staphylinidae) in Nova Scotia, Canada - Moseley, Max; Klimaszewski, Jan; Majka, Christopher G. (Zootaxa, 2006)
The troglophilic staphylinid beetle Quedius spelaeus spelaeus Horn 1871, has been found in a number of porcupine dung caves in Nova Scotia where it appears to be the dominant predator on other invertebrates. In culture, late-instar larvae were observed to excavate and remain in cavities excavated in dung, and to pupate in these cavities. The pupa is described for the first time and compared with other pupae in the genus Quedius Stephens. The apparently disjunct distribution of the species in Nova Scotia is discussed and it is suggested that it may have colonized the province from Atlantic glacial refugia.